The Impact of Perioperative Chemotherapy Timing in Conjunction With Postoperative External-Beam Radiation Therapy on Extremity Soft-Tissue Sarcomas Outcome. (October 2016) - Mahmoud, Omar; Dosch, Austin; Kwon, Deukwoo; Pitcher, John D.; Conway, Sheila; Benedetto, Pasquale; Fernandez, Gustavo; Trent, Jonathan; Temple, H. Thomas; Wolfson, Aaron H.
Abstract : Purpose: The perioperative management of primary extremity soft-tissue sarcomas (ESTS) is multidisciplinary including radiation therapy and chemotherapy (CT). The interplay between these modalities and the relative importance of each remain unclear. Our study aims to determine the relative impact of CT and radiotherapy on the outcome of ESTS patients treated with limb-sparing surgery. Materials and Methods: A retrospective review of ESTS registry yielded 97 patients who received neoadjuvant chemotherapy (NCT) and/or adjuvant CT with or without external-beam radiation therapy (EBRT) from January 1, 1999 through December 31, 2009. The cohort comprised 56 males and 41 females whose age at surgery ranged from 17 to 83 years (median, 56 y). Tumor characteristics included the following: 73 lower ESTS; 70 grade 3 lesions; 63 American Joint Committee on Cancer stage III tumors; and 27 lesions with positive microscopic margins. The following outcome parameters were evaluated for the patients' subgroups: overall survival (OS), locoregional control (LRC), and disease-free survival (DFS). Results: EBRT was delivered postoperatively to 81 patients and 49 received CT. Median EBRT dose was 63 Gy (range, 50 to 72 Gy). At median follow-up of 54.6 months, the 5-year OS, LRC, DFS was 68.9%, 87.1%, 66.5%, respectively. On multivariate analysis, positive surgical margins negatively impacted LRC, DFS, and OS (hazard ratio [HR]=10.43, P =0.004), (HR=2.37, P =0.03), (HR=2.26, P =0.038), respectively. EBRT use improved LRC (HR=0.24, P =0.018) and DFS (HR=0.36, P =0.021). The impact of EBRT on DFS was retained (HR=0.28, P =0.006) in the high-grade ESTS subgroup who received CT. The 5-year local failure rate was 6.5%, 28.6%, and 22.2% ( P =0.019) for patient receiving NCT, adjuvant chemotherapy, and no CT, respectively. Conclusion: Our data support the use of NCT followed by limb-sparing surgery and adjuvant EBRT in ESTS for local failure reduction with a trend toward improved DFS.